Research on residential lifestyles and urban residence pattern’s from the viewpoints of satisfaction, choice, and preference Case study: Tabriz metropolis - Shahrivar Rostaei; Mina Farokhi Someh; Rasoul Ghorbani (نشریه جغرافیا و برنامه‌ریزی, 2023)
IntroductionLifestyle is one of the most popular concepts used to explore consumer behavior. In various fields, the lifestyle concept has been widely used to understand and explain certain consumer behaviors. Residential lifestyle is defined here as the way of life related to residence associated with the consumption of time, space and money. In other words, residential lifestyle is all of the lifestyle factors related to residence. The structure and components of residential lifestyles are comprehensive and complicated, with numerous influencing factors. Here, we propose the concept of residential lifestyles as two-sided properties as individuality and sociality, subjectivity and objectivity, actuality and ideality. Residential satisfaction, Residential environmental choice, and residential preferences are one of the most studied themes in the field of the residential environment. The purpose of this study was to identify the residential choice, satisfaction, and preferences as determined by their lifestyles. A total of 206 usable questionnaires were collected from ten regions in TABRIZ City. Six residential choice factors (Safety, Social, Spaces, and Economical and Education) were derived, and the respondents were grouped into four lifestyle clusters (Urban Cluster, Natural Cluster, Economical Cluster, and Social Cluster). Data and MethodIn this research, we analyzed the characteristics of residential preferential patterns with cluster analysis, residential choice with factor analysis and residential preference and relationship with preferences with factor analysis and hierarchical multi-attribute index system and variance analysis. For the data analysis, descriptive statistics (frequency tables, graphs, percentages, and variance) and inferential statistics (Pearson correlation, ANOVA, T-test) were used. Results DiscussionIn this research, on the basis of the understanding of residential lifestyles and its influence factors, we firstly aimed to interpret the concept through the approach of urban planning as the initial step. Among the factors, we focus on the residential preference, residential emphasis on housing selection, and residential satisfaction as well as the individual attributes such as age, housing ownership, household structure and living years, etc.ConclusionWe have studied residential lifestyles from the perspectives of residential choice factors, residential preference, and residential satisfaction. We have made clear the principal residential choice factors of samples from TABRIZ City. Three subjective residential preferences patterns were obtained: Pattern (1) is the urban preference pattern; (2) is the enjoying life and natural preference pattern; (3) is economical preference pattern and (4) is social preference pattern.